A review on laser machining of alumunia ceramic - Abd Rahman, Md Nizam; Idrus, Bobby Umroh; Ali Mokhtar, Mohd Najib; Ginting, Armansyah; Irianto; Rahimi L, Muhamud; Himawan, Hidayatulah (Suranaree Journal of Science and Technology Office, Suranaree University of Technology, 2023)
Alumina, renowned for its outstanding resistance to corrosion and heat, poses a formidable challenge due to its brittle nature when it comes to machining. Nonetheless, laser machining has emerged as a particularly suitable method for working with hard and brittle materials like alumina. While traditional machining techniques can also be effective, they often necessitate prolonged machining durations and significantly high tool wear rates, thereby driving up the overall machining costs. By employing experimentation and optimization techniques, laser machining technologies such as Nd: YAG lasers, fiber lasers, and CO2 lasers have displayed remarkable efficacy in machining alumina. Notably, CO2 lasers offer distinctive advantages owing to their maximum power output of 45 kW and laser wavelength of 10.6 µm, rendering them suitable for macro material cutting applications. This paper aims to consolidate pertinent information on laser machining of alumina into a single document. The primary focus of this paper revolves around key laser machining parameters, including pulse duration, frequency, peak power, laser power, piercing time, gas pressure, and cutting speed, along with their impact on machining quality aspects such as surface irregularity, kerf width, taper angle, and the Heat-Affected Zone (HAZ).